Alkaline phosphatase levels of murine pre-osteoblastic cells on anodized and annealed titanium surfaces - John Lawrence Ri̇cci̇; Sinem Yeni̇yol (Istanbul University, 2018)
Purpose This study aimed to evaluate the initial adhesion morphology and alkaline phosphatase (ALP) activity of murine pre-osteoblastic MC3T3-E1 cells cultured on anatase/rutile mixed-phase TiO2 thin films with photocatalytical activity with previously confirmed antibacterial properties. Materials and methods Anatase/rutile mixed-phase TiO2 thin films fabricated by anodization and annealing of cpTi were used to culture MC3T3-E1 cells to evaluate the initial cellular adhesion morphology and ALP activity in vitro. Results Compared with MC3T3-E1 cells cultured on cpTi substrates and the control group, cells cultured on anatase/rutile mixed-phase TiO2 thin films exhibited similar ALP levels after cell culture day 9. Conclusion Anodizing and annealing processes fabricate multifunctional surfaces on cpTi with improved osteogenic properties for implants.